An exploratory study on women's innovativeness using gender analysis framework - Rashidah, Shuib (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2018)
The objectiw of this study is to assess the le\Eis of Entrepreneunal Onentation (EO) and women leadership on new innoiE!tion contextualised within institutional and family roles. Women's position at societal and home are multifaceted and their entry in entrepreneurship is often intertw111ed wtth gender roles and mstimional structures Existing EO model is not gender responsiw nor does rt address gender-related constratnts that form barriers to many of women micro-entrepreneurs to access credit and entrepreneurial opportumlies. Addressing the constraints. which are possibly structural or soc1o-cultural, could enhance EO among them. Since women percei~.ed entrepreneunal opportumlies and necess1ties differently than men, increased innovatiw offenngs as economy delefoped. v..-ere motii.eted more by opportunity rather than necessity, and percel..ed opportumties as directly hnked with entrepreneurial capabilities (managenal and leadershtp), the study will haw a strong impact on enhancing women's abilities (sioning and charting) to exploit new opportunities instrumental in entrepreneurship and mo~o~ng the economy up the wlue chain. Additionally. Malaysian women enterpnse owners demonstrated poSilr.e assun1latio'' In entrepreneurial and market orientation dimensions allhough they eXhibited higher than a<.erage fear for failure when compared to Taiwanese and Chinese wornt'fl As most of the local researches mainly focused on SMEs mcluding women entrepreneurs. studying micro-entrepreneurs is lim ely to recognize thelf maJor representation and ownership of the total women's SMEs economy which contnbtnes sigmficantly to Malaysta GOP's growth (32.5